The law of real property - Megarry, Robert 1910-2006; Wade, William (Sweet & Maxwell, 2008)
This new edition of Megarry & Wade's 'The Law of Real Property' presents a definitive textbook on land law. It provides a comprehensive and up-to-date treatment of land law in England and Wales.